Systematic Evaluation of Uranium Impurities in Process Blanks for Ultra-Trace Analysis on Environmental Safeguards Samples using MC-ICP-MS and Isotope Dilution Mass Spectrometry - Ho Lim, Sang; Han, Sun-Ho; Park, Jong-Ho; Park, Ranhee; Lee, Chi-Gyu; Song, Kyuseok (Asian Journal of Chemistry, 2014)
Bulk analysis of environmental swipe samples is a very useful technique to determine the quantities and isotopic ratios of the elements of interest (uranium and plutonium in most cases) at ultra-trace levels. However, it involves tedious chemical procedures, leading to significant amounts of unexpected contaminants causing experimental errors and increasing degrees of uncertainty. Therefore, it is imperative to monitor and evaluate uranium impurities in process blanks to obtain the reliable analytical results at ultra-trace levels. In this work, we have separately estimated the amounts of uranium in a process blank by dividing the process into a chemical pre-treatment step (PBstep1) and chemical separation step (PBstep2) using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) and isotope dilution mass spectrometry (IDMS) technique. In addition, uranium impurities from various possible routes such as chemical reagents and UTEVA resin for chemical separation have also been estimated. The average amount of uranium impurities was 8.73 ± 0.028, 22.34 ± 0.073 and 27.25 ± 0.066 pg for PBstep1, PBstep2 and PBtotal, respectively. Although examinations of the optimization of sample pre-treatment and chemical separation conditions are still in progress, we have confirmed that the estimated values were constantly low and negligible for determining the isotopic ratios and amounts of uranium in environmental swipe samples.